2023
DOI: 10.1021/acs.estlett.3c00521
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Occurrence and Toxicity of 6PPD Quinone, an Emerging Tire Rubber-Derived Chemical: A Review

Khaled Zoroufchi Benis,
Ali Behnami,
Shahab Minaei
et al.

Abstract: -N′-phenyl-p-phenylenediamine (6PPD) is a chemical added to tires to prevent their oxidative degradation. 6PPD is highly reactive with ozone and oxygen, leading to the formation of transformation products such as 6PPD quinone (6PPDQ) on the tire surfaces and, subsequently, in tire and road wear particles. 6PPDQ is a toxicant that has been found in roadway runoff and receiving water systems. Its presence in municipal stormwater has led to the acute mortality of coho salmon during their migration to urban creeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…Our study reported higher concentrations of 6PPD-Q compared to those found in urban runoff from Hong Kong (210–2430 ng/L) and road runoff from Huizhou and Dongguan (38.5–1562 ng/L) . The concentrations of 6PPD were much higher than those reported elsewhere, e.g., 300–14 300 ng/L in a German wastewater treatment plant and 21–130 ng/L in road runoff from Pierce County (USA) . According to Zhou et al, the presence of organic matter and sunlight may enhance the formation of 6PPD-Q in a continuous manner.…”
Section: Resultscontrasting
confidence: 57%
“…Our study reported higher concentrations of 6PPD-Q compared to those found in urban runoff from Hong Kong (210–2430 ng/L) and road runoff from Huizhou and Dongguan (38.5–1562 ng/L) . The concentrations of 6PPD were much higher than those reported elsewhere, e.g., 300–14 300 ng/L in a German wastewater treatment plant and 21–130 ng/L in road runoff from Pierce County (USA) . According to Zhou et al, the presence of organic matter and sunlight may enhance the formation of 6PPD-Q in a continuous manner.…”
Section: Resultscontrasting
confidence: 57%
“…89,90 Given the growing concern regarding tire rubber-derived chemicals and their transformation products, these compounds have received attention in recent dedicated reviews. 17,18,91,92 Tobacco Smoke. Tobacco smoke contains a complex mixture of chemicals, including AAs, which are formed during the combustion of tobacco leaves.…”
Section: ■ Potential Sourcesmentioning
confidence: 99%
“…85,86,191,192 However, most of these studies are limited to method validation, and extensive screenings have not been done. There is growing literature covering tire rubber-associated AAs in surface waters 17,18 given the particular concern about their aquatic toxicity, 80 and increases in surface water concentrations of tire rubberassociated AAs are documented during rain events, which suggests a clear pathway from surface runoff to surface waters. 82 Outside of surface water, quantitative information about AAs is even more limited.…”
Section: T H Imentioning
confidence: 99%
See 1 more Smart Citation
“…Urban air particulate containing tire dusts and dusts from indoor environments, particularly those from facility recycling rubber and electronic waste facilities, also contain 6PPD-Q. Recent reviews summarize the rapidly increasing state of knowledge on sources and levels of 6PPD-Q, its toxicity, and fate. …”
Section: Introductionmentioning
confidence: 99%